(untitled) (Colombia Medica, 2015)
Introduction:Breast Phyllodes tumors are rare breast tumors present in less than 1% of new cases of breast cancer, usually occurring among middle-aged women (40-50 yrs). Objective:This study shows diagnostic experience, surgical management and follows up of patients with this disease during a period of ten years in a oncology referral center. Methods:Retrospectively, breast cancer registries at the institution were reviewed, identifying 77 patients with Phyllodes tumors between 2002 and 2012, who had been operated on at the Instituto de Cancerología - Clínica Las Américas, in Medellín (Colombia). Clinical and histopathological data belonging to these cases was captured and analyzed and descriptive statistics were used. Results:The follow up median was 22.5 months (IQR: 10.5-60.0), average age was 47.2 yrs (SD: 12.4), mean tumor size was 3.6 cm (SD: 4.6), 88.3% of the patients (68 cases) presented negative margins and none of them received adjuvant chemotherapy. Of the patients with Phyllodes tumors; 33.8% had benign, 31.2% had borderline and 35.0% had malignant tumor. Disease-free survival was 85.8% and overall survival was 94.5%. Discussion:Reported data in this article is in accordance with what has been reported in worldwide literature. In our cohort even the high mean size of the tumors, the risk of local relapse and metastatic disease is low than previously reported in literature. Trials with longer follow up and molecular trials in Phyllodes tumors are necessary to understand the behavior of these tumors in Hispanics population.